2007
DOI: 10.1097/wnr.0b013e32815b615b
|View full text |Cite
|
Sign up to set email alerts
|

Microsaccades distinguish between global and local visual processing

Abstract: Much is known about the functional mechanisms involved in visual search. Yet, the fundamental question of whether the visual system can perform different types of visual analysis at different spatial resolutions still remains unsettled. In the visual-attention literature, the distinction between different spatial scales of visual processing corresponds to the distinction between distributed and focused attention. Some authors have argued that singleton detection can be performed in distributed attention, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 19 publications
2
37
2
Order By: Relevance
“…By contrast, salient peripheral cues (visual or auditory, informative or uninformative) that engage exogenous attention might result in microsaccade biases opposite to the cue [72,80,83]. The observation of microsaccade biases opposite to salient and abrupt peripheral events is consistent with inhibition of return [16,75,84,85].…”
Section: Attentional and Cognitive Modulation Of Microsaccadesmentioning
confidence: 56%
See 2 more Smart Citations
“…By contrast, salient peripheral cues (visual or auditory, informative or uninformative) that engage exogenous attention might result in microsaccade biases opposite to the cue [72,80,83]. The observation of microsaccade biases opposite to salient and abrupt peripheral events is consistent with inhibition of return [16,75,84,85].…”
Section: Attentional and Cognitive Modulation Of Microsaccadesmentioning
confidence: 56%
“…Hafed and Clark proposed that microsaccades occur because of subliminal activation of the oculomotor system by covert attention [13]. Since then, there has been consensus that microsaccade rates are modulated by both endogenous (top-down) and exogenous (bottom-up) attentional shifts, with a transient decrease in the rate of microsaccade production approximately 100-200 ms after cue onset, usually followed by a temporary enhancement 300-400 ms after cue onset [8,12,13,61,[72][73][74][75][76][77]. Recent research has linked microsaccade production to other cognitive processes, such as working memory [15,76], and suggested that the absolute frequency of microsaccades is also sensitive to top-down attentional and cognitive modulations [14,78].…”
Section: Attentional and Cognitive Modulation Of Microsaccadesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the case, for example, when simple feature detection is required, so that the visual system can operate on a broader attention scale to simply detect a discontinuity in the visual field. However, if the task requires details of the singleton to be discriminated, like for instance the side on which its shape is truncated, then focused attention needs to be shifted to the corresponding location, as testified by a change in RTs as a function of display numerosity (Bravo & Nakayama, 1992) and of oculomotor activity (Turatto, Valsecchi, Tamè, & Betta, 2007). Within this perspective one could argue that in the T/L task of Experiment 4, as well as in other tasks in which evidence for an involuntary WM-based shift of attention has been documented, target discrimination required focused attention to be shifted to a given position in the display (e.g., Downing, 2000;Olivers et al, 2006;Soto et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a series of studies have been published demonstrating that the preferential direction of microsaccades is inXuenced by the orienting of spatial attention in response to central visual cues (Engbert & Kliegl, 2003;Laubrock, Engbert & Kliegl, 2005;Laubrock, Engbert, Rolfs & Kliegl, 2007; but see Horowitz, Fine, Fencsik, Yurgenson & Wolfe, 2007), peripheral visual and auditory cues (Hafed & Clark, 2002;Rolfs, Engbert & Kliegl, 2004;Galfano, Betta & Turatto, 2004;Betta, Galfano & Turatto, 2007;Rolfs, Engbert & Kliegl, 2005), and during visual search (Turatto, Valsecchi, Tamè & Betta, 2007). Furthermore, the frequency of microsaccades has also been shown to vary as a function of the preparatory state of the manual (Betta & Turatto, 2006) and ocular (Rolfs, Laubrock & Kliegl, 2006) motor systems.…”
Section: Introductionmentioning
confidence: 97%